ANALISIS HUKUM ISLAM DAN HUKUM ADAT DALAM PEMBAGIAN WARISAN DI KELURAHAN JETIS KABUPATEN SUKOHARJO - Anis Rizki Kumara; Muh. Kurniawan BW; Fajri Kurnia Pradana (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2024)
Islamic law also regulates the right to transfer ownership of a person after death to his heirs from all relatives and lineages. Islam details and explains through the Qur'an al-Karim the share of each heir with the aim of realizing justice in society. This research aims to analyze the application of Islamic law and customary law in the distribution of inheritance in Jetis Village, Sukoharjo Regency. This research uses a qualitative method with an analytical descriptive approach to explore the understanding and practices of the community in managing the division of inheritance. Data were collected through in-depth interviews, observations, and document studies, and analyzed using a thematic approach. The results showed that in the Jetis Village community, the division of inheritance is often influenced by a combination of Islamic law and customary law. Although Islamic law provides clear guidelines in terms of inheritance division, local customary practices also play an important role in determining how inheritance is divided among heirs. There is a tendency to adjust the provisions of Islamic law with customary norms to maintain social harmony and accommodate the needs of individuals within the family.